Quizlet application as mooc supportive instrument in teaching Mandarin as a third language in Malaysia - Chua Hui Wen; Mohammad Affiq Kamarul Azlan (2018)
Mandarin has become one of the popular languages to be learnt by non-native Mandarin learners, but the learners always found that learning Mandarin is difficult. Hence, in recent years, Massive Open Online Courses (MOOC) has become gradually popular in language learning as it makes learning become spontaneous, ubiquitous and informal. In this research, a MOOC supportive application called Quizlet was implemented and in the end of the study, a questionnaire in was delivered to students in a university in Kelantan. The research findings show that non-native Mandarin learners demonstrated positive reactions towards the Quizlet application tools applied in MOOC, such as Flashcards, Spell, Learn, Test and Scatter or Match. However, the findings also indicate that there were certain tools such as text audio, picture, exercise and vocabulary, are needed to be developed as part of Quizlet learning tools.